2005
DOI: 10.1007/s00417-005-1176-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of macular carotenoids in relation to age-related maculopathy

Abstract: In this large study, the serum concentrations of L and Z were not related to the prevalence of ARM. However, the large proportion of study participants taking L and/or Z supplementation may have affected these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…From June 2001 to October 2003, a cohort of 1060 individuals from the city of Muenster and the surrounding counties was assembled. [32][33][34] All participants were of Caucasian origin. A cross-sectional analysis of this baseline examination is the basis of the present report.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…From June 2001 to October 2003, a cohort of 1060 individuals from the city of Muenster and the surrounding counties was assembled. [32][33][34] All participants were of Caucasian origin. A cross-sectional analysis of this baseline examination is the basis of the present report.…”
Section: Study Populationmentioning
confidence: 99%
“…32 All digital images were evaluated on a 22-inch computer screen by specially trained technicians. The presence and severity of retinal lesions were graded according to the protocol of the International age-related maculopathy (ARM) Epidemiological Study Group.…”
Section: Examination Procedures and Fundus Photographymentioning
confidence: 99%
“…Although some epidemiological studies have found an inverse correlation between dietary intake and/or serum concentrations of lutein-zeaxanthin and the risk of AMD [16,17,18,19,20,21], a number of investigations have failed to observe this correlation [22,23,24,25,26,27,28]. The largest randomized controlled trial (RCT) in this area so far with a median follow-up of 5 years, the Age-Related Eye Disease Study 2 (AREDS2), evaluated the roles of lutein-zeaxanthin, docosahexaenoic acid (DHA)-eicosapentaenoic acid combinations and a combination of both these formulations, but found no reduction in the risk of AMD progression in any group in a sample of 4,203 participants at risk of progression to advanced AMD [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, and with full appreciation of the limitations of associative studies, there have been no less than 12 cross-sectional reports attempting to investigate the relationship between serum concentrations of macular pigment's constituent carotenoids and the risk for AMD (see Table 2). [20][21][22][23][33][34][35][36][37][38][39][40] Further, and notwithstanding the fact that many of these cross-sectional studies were performed in the pre-AREDS 2 era, it should be appreciated that lutein-containing supplements were commercially available since 1999, 41 and since that date their use grew substantially as a result of widespread dissemination of their putative benefits. [42][43][44][45][46][47][48] Meaningful comment on any such relationship should be predicated, therefore, on population-based studies where data were recorded pre-1999 and to subsequent population-based studies where the use of carotenoid-containing supplements was recorded and appropriately factored into analyses.…”
mentioning
confidence: 99%